Cold Pain Threshold Identifies a Subgroup of Individuals With Knee Osteoarthritis That Present With Multimodality Hyperalgesia and Elevated Pain Levels. Issue 9 (September 2017) - Wright, Anthony; Benson, Heather A.E.; Will, Rob; Moss, Penny
Abstract : Objectives: Cold hyperalgesia has been established as an important marker of pain severity in a number of conditions. This study aimed to establish the extent to which patients with knee osteoarthritis (OA) demonstrate widespread cold, heat, and pressure hyperalgesia. OA participants with widespread cold hyperalgesia were compared with the remaining OA cohort to determine whether they could be distinguished in terms of hyperalgesia, pain report, pain quality, and physical function. Methods: A total of 80 participants with knee OA and 40 matched healthy, pain-free controls participated. OA participants completed a washout of their usual medication. Quantitative sensory testing was completed at 3 sites using standard methods. Cold pain threshold (CPT) and heat pain thresholds (HPT) were tested using a Peltier thermode and pressure pain thresholds (PPT) using a digital algometer. All participants completed the short-form health survey questionnaire and OA participants completed the PainDETECT, Western Ontario and McMaster Universities Osteoarthritis Index of the Knee (WOMAC), and pain quality assessment scale questionnaires. Results: OA participants demonstrated widespread cold hyperalgesia ( P <0.0001), had lower PPT at the index knee ( P <0.0001) compared with controls and reported decreased physical health on the SF-36 ( P =0.01). The OA subcohort with high global CPT (≥12.25°C) exhibited multimodality sensitization compared with the remaining OA cohort (PPT P <0.0001; CPT P <0.0001; HPT P =0.021 index knee). This group also reported increased pain, decreased function, and more features of neuropathic pain. Discussion: This study identified a specific subgroup of patients with knee OA who exhibited widespread, multimodality hyperalgesia, more pain, more features of neuropathic pain, and greater functional impairment. Identification of patients with this pain phenotype may permit more targeted and effective pain management.